Ablation of Toll-like receptor 4 mitigates central blood pressure response during hyperhomocysteinemia. Issue 11 (November 2017) - Jeremic, Nevena; Weber, Gregory J.; Familtseva, Anastasia; Metreveli, Naira; Tyagi, Suresh C.
Abstract : Objective: The objective of this study was to define the mechanisms of homocysteine-induced effects on the aortic wall that promote vascular remodeling and hypertension as well as explore the role of Toll-like receptor 4 in homocysteine-induced effects. Method: Five strains of mice were utilized in this study: C57BL/6J, C3H/HeOuJ, CBS+/−, C3H/HeJ and CBS+/−/C3H. Aorta, heart and blood were collected at the end of the experiments. Blood pressure (BP) was recorded using noninvasive tail cuff method. To determinate effects of vasoactive agent and endothelial-dependent vasodilator on aorta contractility, we performed vascular function measurements. In addition, the expression of mitochondrial fusion and fission proteins, antioxidant markers and collagen fragments were assessed. Results: BP measurements demonstrated a significant increase in SBP and DBPs in CBS+/− mice compared with other groups. CBS+/− mice aorta had lower response to phenylephrine and acetylcholine compared with other groups; however, CBS+/−/C3H mice response was improved. Dynamin-related protein 1 protein expression was significantly upregulated in CBS+/− mice, whereas C3H mice showed downregulation. In addition, CBS+/− mice showed increased oxidative stress, inflammation and decreased nitric oxide. These effects were normalized in CBS+/−/C3H mice. Conclusion: Our findings demonstrate the dominance of endothelial cell mitochondrial fission over mitochondrial fusion in hyperhomocysteinemia and oxidative stress. This may explain the endothelial cell loss and dysfunction that follows collagen deposition, which contributes to inward aorta remodeling in hypertension.